Growth, Employment and Living Standards in Pre-Accession Poland - World Bank (Washington, DC, 2013)
This report builds on the wealth of existing literature on living standards and inequality in Poland and is intended to continue the ongoing debate. The focus is on lack of access to economic opportunities as the most important dimension of poverty in Poland and one that is strongly associated with social exclusion, vulnerability and other dimensions of poverty. The report's main objectives are to: (i) describe what happened to Polish living standards after the "shock therapy" of the early 1990s and in the less prosperous last five years; (ii) highlight the main factors behind the recent increase in poverty and inequality; (iii) identify the main risk factors associated with social exclusion and "transient" and "permanent" poverty in pre-accession Poland; (iv) address the growth of a hard-core of chronic poverty; and (v) point to policy measures that may help Poland to move closer to the Lisbon targets for employment and social inclusion. This report consists of two volumes. Volume 1 presents the main findings and their policy implications. It begins with a general overview of the macroeconomic climate and its changes over the transition period. It then moves on to address the links between economic growth and poverty reduction in the high growth years (when poverty declined considerably) and in the following slow-down in growth (during which poverty increased). A description of the poverty profile and its changes over the last decade follows and leads to an analysis of the strong link between skills levels, employment opportunities and social inclusion as a way of avoiding poverty. Particular attention is paid to the growing divide between the chronically poor and the rest of the population. The role of social transfers as an important safety net for the most vulnerable (but also a potential barrier to effective long-term poverty reduction) is then discussed, along with the role currently played by civil society and informal networks as non-governmental safety nets. Finally some options are presented on policies that may help to meet the European Union targets for employment, social inclusion and reduction in inequalities.